Construction of economic indicators using internet searches - POPESCU, Mioara (Annals of Spiru Haret University. Economic Series, 2015)
The volume of online data searches can be used as indicators of economic analysis and forecasting. This paper reviews some of the applications that use the large data sets provided by the Internet user searches and presents a very specific case for Romanian economy. These data provide some additional information relative to existing surveys and with further development, internet search data could become an important tool for analysis and prediction.